2009
DOI: 10.1161/strokeaha.109.560151
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Screening and Management of Asymptomatic Coronary Artery Disease in Patients With Stroke and Patients With Transient Ischemic Attack

Abstract: Background and Purpose-The feasibility of implementing an expert consensus guideline recommending use of a stroke patient's profile to manage undiagnosed coronary artery disease remains unclear. Methods-Following a guideline-based algorithm, we screened consecutive patients with ischemic stroke and patients with transient ischemic attack for asymptomatic coronary artery disease using the Framingham Heart Study Coronary Risk Score (FCRS) cutoff of high risk (Ն20%) for experiencing a hard coronary artery disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Screening for CAD risk using FRS in ischemic stroke patients has been useful [9,30]. Further, coronary CT has been studied as a noninvasive screening tool for the detection of asymptomatic CAD in high-risk groups, including patients with diabetes or ischemic stroke [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for CAD risk using FRS in ischemic stroke patients has been useful [9,30]. Further, coronary CT has been studied as a noninvasive screening tool for the detection of asymptomatic CAD in high-risk groups, including patients with diabetes or ischemic stroke [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…CCTA provides comprehensive information regarding the location, severity, and characteristics of atherosclerotic plaque, and has been validated against conventional coronary angiography and intravascular ultrasound [13][14][15]. However, the role of enhanced risk stratification using non-invasive imaging studies in stroke patients remains a controversial issue [16,17].…”
mentioning
confidence: 99%
“…A study examining the implementation of this recommendation for poststroke CHD screening found that a minority of eligible patients received testing. 6 When testing was performed, 14% of patients had a positive stress test, with these patients going on to be prescribed β-blockers. 6 While we found that clinicians utilized cardiac stress testing for several approved indications (e.g., chest pain/angina), 21 , 22 our results also demonstrate relative underuse of stress testing among asymptomatic patients with cerebrovascular disease and high-risk FCRS.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although cardiac evaluation among patients with acute or subacute stroke largely focuses on discerning whether an event was caused by a cardioembolic source, 4 the American Heart Association/American Stroke Association (AHA/ASA) also recommends consideration of cardiac screening for asymptomatic CHD based on a high-risk Framingham Cardiac Risk Score (FCRS ≥20%). 3 , 5 - 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation